Outcome Measures in Relapsing-Remitting Multiple Sclerosis: Capturing Disability and Disease Progression in Clinical Trials. (4th May 2014) - Lavery, Amy M.; Verhey, Leonard H.; Waldman, Amy T.
Abstract : Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease that manifests as acute relapses and progressive disability. As a primary endpoint for clinical trials in MS, disability is difficult to both characterize and measure. Furthermore, the recovery from relapses and the rate of disability vary considerably among patients. Given these challenges, investigators have developed and studied the performance of various outcome measures and surrogate endpoints in MS clinical trials. This review defines the outcome measures and surrogate endpoints used to date in MS clinical trials and presents challenges in the design of both adult and pediatric trials.